1998
DOI: 10.1001/archneur.55.9.1226
|View full text |Cite
|
Sign up to set email alerts
|

Seven-Year Survival Rate After Age 85 Years: Relation to Alzheimer Disease and Vascular Dementia

Abstract: In extreme old age, Alzheimer disease and vascular dementia influence the mortality rate considerably. However, mild Alzheimer disease does not influence longevity, at least not during the first 7 years. These findings have important public health implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
64
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 42 publications
12
64
2
Order By: Relevance
“…Patients with dementia have a higher mortality rate, independently of the effects of age and comorbidities [76, 77]. The mortality rate is also increased in patients with PSD [42,78,79,80,81], the relative risk of death ranging from 2.4 to 6.3.…”
Section: Influence Of Psd On Stroke Patients’ Prognosismentioning
confidence: 99%
“…Patients with dementia have a higher mortality rate, independently of the effects of age and comorbidities [76, 77]. The mortality rate is also increased in patients with PSD [42,78,79,80,81], the relative risk of death ranging from 2.4 to 6.3.…”
Section: Influence Of Psd On Stroke Patients’ Prognosismentioning
confidence: 99%
“…Previous studies of populationbased cohort type have evaluated survival in relation to dementia, most reporting that the risk of death is higher in the presence of dementia than in its absence (1)(2)(3)(4)(5)(6). A recent Danish population-based cohort study (14 years of follow-up) involving 3065 non-demented (73.7±6.8 years) and 234 demented (83.3±7.0 years) subjects at baseline, showed that the hazard ratio (HR) of death increased from 1.82 for very mildly demented to 9.52 for severely demented subjects (7).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies, mostly of the population-based cohort type, have evaluated survival in relation to dementia, with most reporting that the risk of death is higher in the presence of dementia than in its absence [5,6,7,8,9,10]. A recent Danish population-based cohort study (14 years of follow-up) involving 3,065 nondemented (73.7 ± 6.8 years) and 234 demented subjects (83.3 ± 7.0 years) at baseline showed that the hazard ratio (HR) of death increased from 1.82 for the very mildly demented to 9.52 for severely demented subjects [11].…”
Section: Introductionmentioning
confidence: 99%